A análise sistemática de fundos imobiliários nacionais e internacionais para investimento - Helfenstein, Luiz Gustavo (2020)
Real Estate Funds pool investor funds and invest in real estate or related securities. Like every investment, they require analysis by the long-term investor who wants to protect their equity. The objective of the research was to establish asset analysis and monitoring model for resource allocation aiming at the protection of assets, through national and international real estate funds, based on fundamentals and management. The methodology used was the hypotheticaldeductive, which established a step-by-step analysis of investment real estate funds in a systematic way. In the example, the funds - XP Malls, FII BTG Pactual, GGR Copevi, Kimco Realty Cp, Alexandria Real Estate and Prologis Inc. - were analyzed through fundamentalist analysis, where their qualitative and quantitative aspects were expressed through indicators, which in their turn. Instead, they were gathered in a table that provides monitoring and comparison between different funds.